Marcelo Rougier (dir.) (2007); Políticas de promoción y estrategias empresariales en la industria argentina 1950–1980, Ediciones Cooperativas, Buenos Aires (304 págs.) - VALERIA IANNI (H-Industri@)
Marcelo Rougier (dir.) (2007); Políticas de promoción y estrategias empresariales en la industria argentina 1950–1980, Ediciones Cooperativas, Buenos Aires (304 págs.)